Observation of Failure Scenarios in Riveted Assemblies: An Innovative Experimental Strategy. (2015) - Sire, S.; Mayorga, L. Gallegos; Plu, B.
Abstract: Hot riveting was largely used as method of assembly in France during the appearing and expansion of the railway network (1840- 1940). Present in wrought iron and steel constructions, riveted connections are commonly found in the French railway heritage. Conceived as a permanent assembly, these connections work by the shearing of the rivets and the friction between the plates, such friction is caused by the clamping force due to the cooling of the rivet after forging. The mechanical behavior of the assembly will depend on the many parameters involved in the process. However, three main failure modes have been identified: tension on the plates, shearing of the rivet and bearing in the plates (pressure of rivet on the rivet hole). To understand the influence of friction in the global behavior of the assembly, a comparison between two types of S235 steel specimens is proposed. The first was a set of several hot riveted specimens and in the second one, the rivet was replaced by a martensitic stainless steel axis with a high yield stress that kept the pieces of the connection in place (no clamping force was thus present this time). The behavior of both types of specimens was then studied in tension using 3D Digital Image Correlation to analyze local and global displacements. The comparison between the relative displacements of the connected plates of the two types of specimens allows identifying the influence of friction in the global behavior. To complete this kinematics investigation, failure scenarios are described through longitudinal cross sections analysis.